Pendidikan Anak Pada Usia Dini - Aidil Saputra (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
Early childhood education is a coaching effort aimed at children from birth up to the age of six who is done through the provision of educational stimuli to help the growth and development of physical and spiritual, so that children have readiness in entering further education. The development of education begins at birth.Babies should be introduced to the people around them, voices, objects, invited to joke and talk so they can grow into normal and healthy children. The method of learning appropriate to the years of birth until the age of six years usually determines the child’s personality as an adult.Education at this time is a coaching effort aimed at children from birth up to the age of six, which is done through the provision of stimuli. In educational institutions of early childhoodeducators are required to develop the potential of children, so that later children are able to deal with creative issues.